The Effectiveness of Providing Legal Aid to the Poor in West Kalimantan Province During the Covid-19 Pandemic - Yustika Irianita Fanty (Jurnal Dinamika Hukum, 2022)
The implementation of policies issued by the Government to overcome the Covid-19 Pandemic has an impact on the provision of Legal Aid services by Legal Aid Providers to Legal Aid Recipients in West Kalimantan, the effectiveness of providing legal aid to the community. This research is juridical-normative. Sources of legal materials consist of primary data and secondary data which include primary and secondary legal materials. The technique of data collection is by collecting primary data through interviews with resources and data from the Legal Aid Administration System of the National Law Development Agency, secondary data collection through literature and document study methods. The results of the research that focus on the provision of legal aid by Legal Aid Providers in West Kalimantan are the policies taken by the Government in tackling the Covid-19 Pandemic, whether in the form of limiting community crowds or hearings and online visits for correctional inmates, which have quite an impact on the provision of legal aid. However, it does not reduce the effectiveness of the implementation of the provision of legal aid to fulfill the right to access to law and justice for the community, especially the poor in West Kalimantan during the Covid-19 Pandemic.Keywords: legal aid recipient; obstacle in providing legal aid; providing legal aid